IMPLEMENTASI PROGRAM BERAS SEJAHTERA - Nela Roza, Sujianto, Harapan Tua R.F.S (Universitas Riau, 2019)
Implementation of the Prosperous Rice Program. The purpose of this study was to find out and analyze the implementation of a prosperous rice program in Talang Gedabu Village, Rakit Kulim District, Indragiri Hulu Regency. This study uses a qualitative descriptive research method. The sources of data in this study were the Village Literature Implementation Team, Inner Board, Hamlet Head, and several Beneficiary Families (KPM) in Talang Gedabu Village. And data analysis is done through data reduction, data presentation and drawing conclusions. The results of the implementation of the prosperous rice program are inaccurate, in the sense that the free rice assistance provided by the government is still inaccurate and not in accordance with those who really have the right to receive it. This can be said because of the five indicators as the success of the prosperous rice program based on TNP2K, only one indicator is right.